2021
DOI: 10.3390/genes12122013
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics View over the Germination Landscape in Biofortified Rice

Abstract: Hidden hunger, or micronutrient deficiency, is a worldwide problem. Several approaches are employed to alleviate its effects (e.g., promoting diet diversity, use of dietary supplements, chemical fortification of processed food), and among these, biofortification is considered as one of the most cost-effective and highly sustainable. Rice is one of the best targets for biofortification since it is a staple food for almost half of the world’s population as a high-energy source but with low nutritional value. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…In recent years, the rapid development of high-throughput sequencing technology has resulted in the emergence of transcriptome analysis by RNA sequencing as a powerful strategy to explore molecular mechanisms underlying complex biological processes [32,33]. In this study, we found that the NGP4A mutation caused global changes in the rice transcriptome using RNA sequencing.…”
Section: Discussionmentioning
confidence: 71%
“…In recent years, the rapid development of high-throughput sequencing technology has resulted in the emergence of transcriptome analysis by RNA sequencing as a powerful strategy to explore molecular mechanisms underlying complex biological processes [32,33]. In this study, we found that the NGP4A mutation caused global changes in the rice transcriptome using RNA sequencing.…”
Section: Discussionmentioning
confidence: 71%
“…Given that priming protocols are known to be not only species-but also genotype-specific [29,33], a collection of 11 rice varieties, representative of indica and japonica groups, typically grown under lowland or upland conditions, respectively, were used in this study. Moreover, because rice germination can be affected also by the grain mineral content [41], high Zn or Fe biofortified lines were incorporated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To address the genotype specificity of most seed priming protocols [29,33], we used 11 rice varieties with different grain mineral contents, belonging to japonica and indica subgroups, representative of lowland and upland ecosystems. Biofortified rice lines with enhanced zinc (Zn) and iron (Fe) grain content, developed through conventional breeding [37,38], transgenic approaches [39], and genome editing (GEd) [40], were also investigated due to putative alterations in the germination behavior [41].…”
Section: Introductionmentioning
confidence: 99%
“…Parray et al improved the accumulation of sesame 2S albumin-boosted cysteine and methionine levels in genetically manipulated rice seeds [ 110 ]. Dai et al biofortified soybeans with glycine [ 111 ], Yang et al [ 112 ] reported enhanced free lysine content in rice seeds, Dueñas et al reported increased accumulation of tryptophan transgenic rice seeds [ 113 ] and Tiong et al overexpressed aspartate aminotransferase genes in rice, resulting in induced amino acid content in rice seeds [ 114 ]. Yang et al used a combination of transgenic events to develop two pyramid transgenic lines (High Free Lysine; HFL1 and HFL2) with more than 20-fold higher free lysine levels in rice seeds than in the wild type [ 115 ].…”
Section: Nutrients Used In Biofortificationmentioning
confidence: 99%